2023
DOI: 10.34133/research.0086
|View full text |Cite
|
Sign up to set email alerts
|

PDGFR in PDGF-BB/PDGFR Signaling Pathway Does Orchestrates Osteogenesis in a Temporal Manner

Abstract: Platelet-derived growth factor-BB (PDGF-BB)/platelet-derived growth factor receptor-β (PDGFR-β) pathway is conventionally considered as an important pathway to promote osteogenesis; however, recent study suggested its role during osteogenesis to be controversial. Regarding the differential functions of this pathway during 3 stages of bone healing, we hypothesized that temporal inhibition of PDGF-BB/PDGFR-β pathway could shift the proliferation/differentiation balance of skeletal stem and progenitor cells, towa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…PRP is enriched with various growth factors, including VEGF, TGF, and PDGF. Previous studies have shown that these growth factors promote osteocyte proliferation (Wu et al, 2016;Hu and Olsen, 2017;Wang et al, 2023). Therefore, in the CCK-8 test, cell proliferation on the surface of the samples in each group incubated with PRP was significantly higher than that in the non-incubated group.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…PRP is enriched with various growth factors, including VEGF, TGF, and PDGF. Previous studies have shown that these growth factors promote osteocyte proliferation (Wu et al, 2016;Hu and Olsen, 2017;Wang et al, 2023). Therefore, in the CCK-8 test, cell proliferation on the surface of the samples in each group incubated with PRP was significantly higher than that in the non-incubated group.…”
Section: Discussionmentioning
confidence: 83%
“…Although PDGF is a recombinant growth factor approved by the FDA for clinical use to promote bone regeneration, recent studies have shown that PDGF-BB alone does not significantly directly promote bone defect repair (Luvizuto et al, 2016;de Oliveira et al, 2017;Bai et al, 2020). However, studies have shown that PDGF-BB contributes to osteocyte proliferation and intraosseous angiogenesis (Wang et al, 2023). Studies have shown that TGF-β can promote the proliferation, chemotaxis, and early differentiation of osteoprogenitor cells through the Smad pathway and inhibit osteoclast differentiation by downregulating the RANKL/OPG secretion ratio (Wu et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…PDGF-BB)/PDGFR-β pathway is generally considered an important pathway for promoting bone formation. PDGF-BB, as a growth factor derived from platelets, is regarded as a key factor in the pathological bone formation of AS ( 47 , 48 ). The relationship between IFN-γ and AS has been extensively studied.…”
Section: Discussionmentioning
confidence: 99%
“…The processes governing regeneration predominantly encompass cell proliferation, migration, differentiation, and the precise patterning of regenerating tissues and organs [ 218 , 219 ]. Cell proliferation serves as the foundational process, where new tissues or organs arise through cellular division and propagation [ 220 223 ]. Cell migration involves the movement of cells from one location to another, establishing the correct structural arrangement [ 221 , 224 , 225 ].…”
Section: Spatiotemporal Multi-omics Techniques In Regeneration Studiesmentioning
confidence: 99%